RISK FACTORS FOR PREECLAMPSIA INCIDENTS AT PROF. DR. MARGONO SOEKARJO HOSPITAL AUGUST 2023 – JULY 2024 - Keysa Putra Syahrinto; Yudhi Wibowo; Edy Priyanto; Herman Sumawan; Amalia Muhaimin (Mandala Of Health, 2026)
Background: Preeclampsia is the leading cause of maternal death in Central Java in 2023. Preeclampsia is known to be associated with risk factors such as gemelli, maternal age, gravida, parity, diabetes mellitus (DM), and maternal nutritional status before pregnancy, although there are still differences in the relationship values ​​​​in several research center. Therefore, research is needed to determine the relationship of preeclampsia risk factors with the incidence of preeclampsia at RSUD Prof. Dr. Margono Soekarjo. Objective: This study aims to determine the relationship between maternal nutritional status before pregnancy, DM, maternal age, gravida, parity, and gemelli with the incidence of preeclampsia at RSUD Prof. Dr. Margono Soekarjo August 2023 – July 2024. Methodology: This study was conducted using a cross-sectional study design with a sample of 392 pregnant women. The independent variables in this study were gemelli, maternal age, gravida, parity, DM, and maternal nutritional status before pregnancy, the dependent variable was the diagnosis of preeclampsia, and the potential confounding variable controlled was bacteriuria. Results: The results of multivariate analysis showed that gemelli (p= 0.008), age <20 years (p= 0.009), age >35 years (p<0.001), overweight (p<0.001), obesity (p<0.001), chronic energy defficient (p<0.001), nulliparous (p<0.001), and multiparous or grandemultiparous (p<0.001) were significantly associated with the incidence of preeclampsia at RSUD Prof. Dr. Margono Soekarjo in August 2023 – July 2024. Conclusion: Gemelli were the risk factor that most influenced the incidence of preeclampsia at RSUD Prof. Dr. Margono Soekarjo in August 2023 – July 2024.